Conduction Mechanism by Using CBH Model in Fe3+ and Mn3+ Ion Modified Pb(Zr0.65−xAxTi0.35)O3 (A = Mn3+/Fe3+) Ceramics. (18th March 2013) - Sahu, Niranjan; Panigrahi, S.; Kar, Manoranjan
Abstract : Polycrystalline samples of manganese and iron substituted lead zirconium titanate (PZT) with general formula Pb(Zr0.65− x A x Ti0.35 )O3 (A = Mn 3+ and Fe 3+ ) ceramics have been synthesized by high temperature solid state reaction technique. X-ray diffraction (XRD) patterns were recorded at room temperature to study the crystal structure. All the patterns could be refined by employing the Rietveld method to R3c space group with rhombohedral symmetry. Microstructural properties of the materials were analyzed by scanning electron microscope (SEM), and compositional analysis was carried out by energy dispersive spectrum (EDS) measurements. All the materials exhibit ferroelectric to paraelectric transition. The variation of dielectric constant and loss tangent with temperature and frequency is investigated. The decrease of activation energy and increases of AC conductivity with the Fe 3+ or Mn 3+ ion concentration have been observed. The AC conductivity has been analyzed by the power law. The frequency exponent with the function of temperature has been analyzed by assuming that the AC conduction mechanism is the correlated barrier hopping (CBH) model. The conduction in the present sample is found to be of bipolaron type for Mn 3+ ion-doped sample. However, the conduction mechanism could not be explained by CBH model for Fe 3+ ion-doped sample.